Challenges and barriers faced by women in accessing justice against obstetric violence - Majety, Chandramathi; Bejugam, Sravani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The progress of any nation exclusively depends on the societal status of women. Just about one half of the global population comprise of women. Women have always been sufferers of abuse by male dominated society. Men require being oriented about their sense of duty towards women and women wishes to be empowered. The position remains the same everywhere. In a country like India woman is worshipped as goddess and on the other hand she is being subjected to oppression, suppression, exploitation and ill-treated by the male dominated society. The United Nations report states that “woman constitutes half of the world population, perform nearly 2/3 of works hours, receive one tenth of the world’s income and own less than one-hundredth percent of the world’s property.” There are many probable retort to the problem of violence against women and a range of legal doctrines in which violent behavior come into sight as an issue. A wholesome legal response to crime against women might require a significantly restructured legal framework with a new approach solely for the rationale of dealing with violence against women in all its forms. “Obstetric violence” refers to acts categorized as physically or psychologically violent in the process of child birth. Obstetric care submits to the most basic maternal care. It deals itself with the concern of a woman during pregnancy, childbirth and the post-partum blues. This also involves providing information regarding the pregnancy, child birth and post-partum blues. Indian Public Health Standards guides ‘emergency obstetric care’ as an essential service at every government health care center. Most of the findings have decorated the situation of obstetric care in the government health facilities to be of very poor quality and the major concern of maternal mortality. Legal intervention must ensure women’s reproductive rights for better implementation and monitoring of schemes and to push the government to consider reproductive rights as a part of human rights in its realization.